INDONESIA'S EFFORTS IN FACING TARIFF AND NON-TARIFF BARRIERS ON SHRIMP EXPORTS TO GERMANY - Puspita, Syifa Rifda; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
One of the potential fishery commodities to be exported due to high demand in the international market is shrimp. However, the European Union as the main importer of shrimp applies high tariffs and demands that exporting countries comply with the Council Regulation. These tariff and non-tariff barriers have led to a decline in exports in Indonesia. To maintain its market in the European Union, Indonesia must find ways to continue exporting its shrimp products, especially to Germany, because Germany is the eighth largest importer of shrimp products in Europe. The efforts made by the Indonesian government to maintain shrimp exports to Germany will be described in this study.This research uses descriptive qualitative method. The perspective used by the author in this thesis is the perspective of liberalism by Adam Smith with the level of nation state analysis, and the theory used is the theory of international trade by David Richardo. To analyze this, the authors collected data from books, journals, websites, as well as various information from the relevant European Union official website, the Ministry of Trade of the Republic of Indonesia, and the Ministry of Maritime Affairs and Fisheries of the Republic of Indonesia regarding Indonesia's efforts to increase shrimp exports to Germany.The results of this study indicate that Indonesia seeks to increase shrimp exports to Germany by lobbying for a reduction in export tariffs for fishery products including shrimp with the European Union by the Director General of Strengthening the Competitiveness of Marine and Fishery Products. Improving the quality and cleanliness in the management of Indonesian shrimp is also carried out through the implementation of the clustering system, the Participatory Pond Irrigation Management program (PITAP), the revitalization of shrimp ponds, and also the implementation of the Indonesian Good Aquaculture Practice (IndoGAP) scheme. Although there has not been an increase in the export value, there has been an increase in the quality of Indonesian shrimp. So, Indonesia can re-increase the confidence of the European Union, especially Germany, in Indonesian shrimp.Keywords: International Trade, European Union, European Commission.Â